Solidification of Earth’s mantle led inevitably to a basal magma ocean - Charles-Édouard Boukaré; James Badro; Henri Samuel (Nature, 2025)
Abstract One of the main interpretations of deep-rooted geophysical structures in the mantle1 is that they stem from the top-down solidification of the primitive basal magma ocean of Earth above the core2–6. However, it remains debated whether solids first formed at the bottom of the mantle, solidifying upward, or above the melts, solidifying downward. Here we show that gravitational segregation of dense, iron-rich melts from lighter, iron-poor solids drives mantle evolution, regardless of where melting curves and geotherms intersect. This process results in the accumulation of iron-oxide-rich melts above the core, forming a basal magma ocean. We numerically model mantle solidification using a new multiphase fluid dynamics approach that integrates melting phase relations and geochemical models. This enables estimating the compositional signature and spatial distribution of primordial geochemical reservoirs, which may be directly linked to the isotopic anomalies measured in Archean rocks7–11. We find that a substantial amount of solids is produced at the surface of the planet, not at depth, injecting geochemical signatures of shallow silicate fractionation in the deep mantle. This work could serve as a foundation for re-examining the intricate interplay between mantle dynamics, petrology and geochemistry during the first thousand million years of the evolution of rocky planets.